Reactive Voltage Control of Wind Farm Based on Tabu Algorithm - Ren, Xin; Wang, Hua; Wang, Zhongchao; Wang, Qijiang; Li, Bangxing; Wu, Hao; Yang, Jian; Wang, Wei (Frontiers in Energy Research, 2022)
In view of the current wind farms are mostly multi-wind turbines, and it is difficult to accurately control a single wind turbine, the paper proposes a reactive power and voltage coordinated control strategy suitable for doubly-fed wind farms. The strategy is mainly divided into three layers. The first is the field group layer, which can obtain the reactive power compensation task of the entire field group according to the current voltage and voltage indicators of the field group collection station. The second is the field layer, according to the reactive power compensation tasks issued by the field group layer, the reactive power tasks are allocated to each field area based on the tabu search algorithm or the equal margin method. The third is the equipment layer, which allocates equal margins in the area according to the reactive power compensation tasks assigned by the field layer. At the field layer, this paper divides 66 wind turbines into 5 field areas to solve the reactive power compensation distribution task according to the voltage sensitivity characteristics of the wind turbines on different feeders.